Prevotella as the hub of the cervicovaginal microbiota affects the occurrence of persistent human papillomavirus infection and cervical lesions in women of childbearing age via host NF‐κB/C‐myc. Issue 11 (30th July 2022) - Dong, Binhua; Huang, Yuxuan; Cai, Hongning; Chen, Yaojia; Li, Ye; Zou, Huachun; Lin, Wenyu; Xue, Huifeng; Feng, Anping; Zhao, Heping; Lu, Yanfang; Gao, Hangjing; et al.
Abstract: There is evidence that coinfection of cervicovaginal high‐risk human papillomavirus (HR‐HPV) and bacteria is common in women of childbearing age. However, the relationship between bacterial vaginosis (BV) and persistent HR‐HPV infection in women of childbearing age and the underlying mechanisms remain unclear. In this study, we determined whether BV affects persistent HR‐HPV infection in women aged 20–45 years and explored the possible mechanisms of their interactions. From January 1 to April 30, 2020, we recruited women aged 20–45 years with and without BV at a ratio of 1:2 from Fujian Maternity and Child Health Hospital. All women were followed up at 0, 12, and 24 months. A BV assay, HR‐HPV genotyping and cervical cytology were performed at each follow‐up. At 0 months, additional vaginal secretions and cervical exfoliated cells were collected for 16S ribosomal RNA sequencing, bacterial metabolite determination, and POU5F1B, C‐myc, TLR4, NF‐κB, and hTERT quantification. A total of 920 women were included. The abundance of Prevotella ( p = 0.016) and Gardnerella ( p = 0.027) were higher, whereas the abundance of Lactobacillus was lower ( p = 0.001) in women with persistent HR‐HPV infection and high‐grade squamous intraepithelial lesions (HSIL). The abundance of Prevotella ( p = 0.025) and Gardnerella ( p = 0.018) increased in the vaginas of women with persistent HPV16 infection, whereas only the abundance of Prevotella ( p = 0.026) was increased in women with persistent HPV18 infection. The abundance of Prevotella in the vagina was significantly positively correlated with the expression levels of TLR4, NF‐κB, C‐myc, and hTERT in host cervical cells ( p < 0.05). Our findings suggest that overgrowth of Prevotella in the vagina may influence the occurrence of persistent HR‐HPV infection‐related cervical lesions through host NF‐κB and C‐myc signaling.